Dolomite Origins of the Carbonate Successions From the Chihsia Formation, South China: A Case Study From the Pingdingshan Section - Kuang, Hao; Mao, Zhenxing; Zhuo, Xiaojing; Li, Mengkang; Liu, Chao (Frontiers in Earth Science, 2022)
The carbonate successions from the Chihsia Formation play an important role for hydrocarbon exploration in the South China. However, the dolomites occurring in the upper section of the Chihsia Formation have been enigmatic, which confined further understanding of the depositional and/or diagenetic fluids and hydrocarbon prediction. In this study, the Pingdingshan section was investigated as a typical outcrop of Chihsian carbonates. On the basis of petrologic/mineralogic observation of hand specimens and thin-sections, three types of dolomites were classified according to their crystal sizes, i.e., micritic dolomite, surcosic dolomite, and saddle dolomite. Comprehensive, micro-area geochemical proxies, including homogenization temperatures of fluid-inclusions, carbon and oxygen isotopes, trace and rare-earth elements were analyzed on different types of dolomites and matrix calcites. The results revealed that the selected samples were representative to temporal seawater and were not contaminated by terrestrial input. The temperatures and salinities of fluid-inclusions, combined with carbon and oxygen isotopic values, revealed that sucrosic dolomites originated from penecontemporaneous micritic dolomites, which had been crystallized and altered into fine- or medium-sized dolomite clusters during later-stage burying process. By contrary, the saddle dolomites occurring in carbonate matrix or fractures were formed at a hydrothermal environment with temperature of dolomitizing fluid higher than 170 ℃. This inference is consistent with evidences from rare-earth elements and carbon and oxygen isotopes. Our findings provide new clues for origin elucidation of dolomitizing fluids in the Chihsia Formation, South China.